Bioconversion of agro-industrial wastes: Combined compost and vermicompost processes using Eisenia fetida for stabilization of poultry litter - Masin, Carolina Elisabet (2020)
In this study, a combined treatment of composting and vermicomposting of poultry litter (PL), rice hulls (RH) and/or eucalyptus sawdust (ES) is carried out in order to obtain a high-quality organic fertilizer and avoid the environmental problems associated with the use of raw poultry manure and fresh agricultural waste materials. Methods The three composts mixtures were obtained mixing the individual waste organic materials in the following volume proportions: 1:3 RH/PL (M1); 1:2 ES/PL (M2) and 0.5:1:2 RH/ES/PL (M3). A second stage of vermicomposting using earthworms (Eisenia fetida ) was also applied. Physicochemical and biological parameters were recorded throughout the 120 days of composting and the 90 days of vermicomposting of the mixtures. Phytotoxicity tests were also performed at the end of the composting and vermicomposting times by means of Lactuca sativa, L. seed germination, to compare the quality of the organic fertilizers obtained. Results The combined treatment of composting and vermicomposting enhances the properties and quality of the final products, particularly electrical conductivity was markedly lower in all vermicomposts. Also, Germination Index values in vermicomposts were greater than 60% indicating the high quality of the product obtained, being the mixture 0.5RH:1ES:2PL that showed better quality and higher maturation degree. Conclusion The system that combines both processes (composting+vermicomposting) was effective to produce a stabilized organic fertilizer from poultry litter with other waste organic materials.